2001년 11월 오염시기와 2002년 봄 황사시기 제주도 고산에서의 잔류성 유기오염물질 농도 변화 - 김영성; 김진영; 김연제; 문길주; 문광주; 한진석; 김상우; 윤순창; 권성안 (한국대기환경학회, 2003)
Atmospheric concentrations of persistent organic pollutants (POPs) were measured at Gosan, Jeju in November2001 and spring 2002, each time for two weeks. Primary target pollutants were organochlorine pesticides, coplanarpolychlorinated biphenyls(co-Polycyclic aromatic hydrocarbons(PAHs) were also measured in order to understand the overall characteristics ofthe POPs distribution as well as PM2.5, a potent carrier of POPs. In the latter part of the measurement period ofNovember 2001, almost every pollutant of combustion origin including dioxin/furans went high probably due toinuence of emissions in the nearby area. The characteristics of atmospheric environment at Gosan in this periodthe end of the measurement period of spring 2002. However, changes in pollutant concentrations were relativelysmall except PM10. Nevertheless, increases in particulate PAHs and OCDD (octachlorinated dibenzo-p-dioxins),mostly present in ne particles, were observed. Trends in organochlorine pesticide variations were mixed although possible volatilization of DDT residues from soil was inferred from the measurements of spring 2002.